Vulnerable Practice: Why We Need Honest Conversations To Make Change (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
As practitioners who have been involved in work that draws on traditions of critical education in community settings, frustration, isolation, hope, and connection have been central emotions in our experiences.  We feel frustrated by limited resources and the enormity of the task, isolated in the work we are doing and the conditions we are trying to do it in, and over whelmed by the devastating realities we see in and across communities.   We also feel deeply connected to the communities we work alongside and we feel connection in the chance meetings with other like-minded/like-purposed people we meet. We feel sure that critical education is a necessary part of changing the intolerable – but we don’t feel sure about how to make critical education an effective and sustainable practice in the current context.  So how do we find out?  In this article we will argue that there is a need to build spaces and relationships that allow for more honest conversations and greater vulnerability about the challenges involved in doing critical education.  We believe that these spaces and relationships need to be supportive and they need to connect dialogue with collective action.  We will share with you a bit about CAMINA, a project which is trying to nurture such conversations and link them to action, but which also faces its own challenges in doing so.